2021
DOI: 10.1371/journal.ppat.1009310
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogenic E. coli induces DNA damage in the bladder

Abstract: Urinary tract infections (UTIs) are among the most common outpatient infections, with a lifetime incidence of around 60% in women. We analysed urine samples from 223 patients with community-acquired UTIs and report the presence of the cleavage product released during the synthesis of colibactin, a bacterial genotoxin, in 55 of the samples examined. Uropathogenic Escherichia coli strains isolated from these patients, as well as the archetypal E. coli strain UTI89, were found to produce colibactin. In a murine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Additionally, uropathogenic E. coli strains carrying the pks island have also been described. Chagneau et al (2021) detected colibactin in 24.7% of urine samples from patients with community-acquired pyelonephritis, cystitis or asymptomatic bacteriuria ( Chagneau et al, 2021 ). They also reported that colibactin was produced during UTIs and induced DNA damage in urothelial cells ( Chagneau et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, uropathogenic E. coli strains carrying the pks island have also been described. Chagneau et al (2021) detected colibactin in 24.7% of urine samples from patients with community-acquired pyelonephritis, cystitis or asymptomatic bacteriuria ( Chagneau et al, 2021 ). They also reported that colibactin was produced during UTIs and induced DNA damage in urothelial cells ( Chagneau et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Chagneau et al (2021) detected colibactin in 24.7% of urine samples from patients with community-acquired pyelonephritis, cystitis or asymptomatic bacteriuria ( Chagneau et al, 2021 ). They also reported that colibactin was produced during UTIs and induced DNA damage in urothelial cells ( Chagneau et al, 2021 ). Similarly, the study conducted by Morgan and collaborators in an in vivo model of ascending UTI in rats, showed that isolates carrying the cnf-1 , clbA and clbQ genes induced severe UTIs within 48–72 h ( Morgan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria frequently colonize extraintestinal sites and colibactin mutational signatures have been reported in a subset of patients with head and neck, urinary tract, neuroendocrine tumors, and ovarian cancer [ 9 ]. A higher concentration of colibactin biosynthetic byproducts in the urine of patients with urinary tract infection (UTI) relative to healthy individuals, and an archetypal UTI strain of pks + E. coli causes DNA damage within the regenerative compartment of the bladder after transurethral infection in mice, suggesting a potential role for these microbes in bladder cancer [ 75 ]. Two separate studies currently published as pre-prints have identified a high proportion of pks + E. coli in association with DNA damage in biopsies from prostate cancer patients [ 76 ] and pks + Klebsiella pneumoniae in a subset of hospital patients with liver abscess [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we should also recognize that the presence of pks + E. coli may be not enough for the development of CRC but exhibits its carcinogenic role under certain conditions such as inflammation. DNA damage caused by colibactin has been observed in cellulo [10][11][12] and in mouse models of digestive or urinary tract colonization [5,[13][14][15][16][17][18][19]. The consequences for cells infected by pks + E. coli depend on the infection dose: A high infectious dose induces massive DNA damage, resulting in mitotic catastrophe and apoptosis [11,12,19], whereas a milder infectious dose induces persistent DNA damage and senescence [16,49].…”
Section: Pks + E Coli Induce Dna Damage and Have A Mutational Impact In Colorectal Cancermentioning
confidence: 99%
“…Colibactin is a secondary metabolite belonging to the chemical family of hybrid polyketide (PK)-nonribosomal peptides (NRP). Colibactin directly damages host DNA both in vitro [10][11][12] and in vivo [5,[13][14][15][16][17][18][19]. This genotoxin is linked to the virulence of pathogenic E. coli [15,17,20], intestinal microbial diversity [21] and intestinal homeostasis [5,22].…”
Section: Introductionmentioning
confidence: 99%